Nursing Home Certificate of Need Moratoria During the COVID-19 Pandemic Had Little Impact on Access - Anthony Yu PhD; Christopher Whaley PhD (SAGE Publishing, 2024)
In over half of US states, health planning boards monitor and control the supply of health care through certificate of need (CON) laws. The COVID-19 pandemic led several states to impose moratoria on CON regulations, hoping to bolster hospital and skilled nursing facility (SNF) beds. Using a difference-in-difference research design, we leverage 2015 to 2021 cost report data from SNFs to study the association between COVID-related CON moratoria and health care supply. Counties that imposed moratoria experienced a slight decline in per-capita SNF bed count. However, once adjusted for potential differential shocks in pre-pandemic high utilization counties, we find little evidence that moratoria led to increased nursing home capacity, overall or by urbanicity. In the context of nursing homes, we conclude that CON deregulation was relatively ineffective at mitigating pandemic-era supply concerns.